Useful Ornaments: Form and Function at Demill Ladies’ College - Suchan, Laura (Ontario History, 2016)
The Reverend Demill opened his boarding school, Demill Ladies’ College in Oshawa, Ontario, in 1876 to offer higher education to young girls in a non-denominational setting. Demill’s vision, to offer a superior educational experience to ensure young women became useful members of society, draws into question the form and function of female education in the late 19th century. This article assesses the curriculum, faculty, moral environment and student success at Demill Ladies College to determine if an education at Demill was supporting the expected role of women in the private sphere or did it provide opportunity for young ladies to pursue opportunities in the public sphere.